COKLAT MALIBOU DALAM PENCIPTAAN KARYA FOTOGRAFI PRODUK - GUSTI, SITI MARJANI (Matalensa: Journal of Photography and Media, 2021)
Photography commercial is photography whose aim is to promote goods or services, here the artist raises Chocolate Malibou in the creation of the Photography Product as the title of the invention of photography. Malibou Chocolate product in product photography is a photographic work that clearly describes a product or item that is intended to promote the product to be sold. The value side of a product is packed in an attractive secrete to attract consumers to progress. To promote an identical item accompanied by a photograph of the product. Product Malibou Chocolate is very suitable chocolate produced in combination with a variety of foods and drinks. The superiority of malibou collars high in antioxidant Chocolate Malibou is very good for heart health. The creation of this final task requires a veritable stage in its creation. In the first process it covered preparation of the elaboration, synthetic, conceptual realization and completion. The process of photographing this final assignment begins with the idea and concept, the selection of supporting properties accompanied by the lighting of created an interesting photographic work.